KEMAMPUAN BERPIKIR KREATIF SISWA ASIMILASI (ASSIMILATING) DAN KONVERGEN (CONVERGING) DALAM MEMECAHKAN MASALAH NUMERASI - Chusnul Fadlilah; Tatag Yuli Eko Siswono (MATHEdunesa, 2022)
Abstract The creative thinking ability is an individual’s capacity in combining logistical and divergent thinking in finding solutions to a problem to produce innovative new products. This study aims to analyze the level of creative thinking ability (LCT) of students with assimilating and converging learning styles in solving numeracy problems. The subjects of this qualitative research consisted of two grade VIII junior high school students who were selected using a purposive sampling technique, namely subjects who had assimilating and convergent learning styles. The research instrument consisted of a learning style questionnaire, a numeracy creative thinking ability test, and task-based interviews. The indicators used to assess creative products include fluency, flexibility, and novelty. Data analysis uses Pierce's triadic analysis or Peirce's semiotics which is the relationship between sign/representamen (which represents something else), object (which describes it), and interpretant (possible meaning or meaning made from it). The results showed that subjects with assimilating learning styles had creative thinking ability with LCT 3 (creative) because they met the indicators of fluency, flexibility and novelty. Meanwhile, students with convergent learning styles have the ability to think creatively with TKBK 2 (creative enough) because they meet the indicators of fluency and flexibility. Even though they did not meet the indicators of the results’s novelty, the students had reached the novelty of ideas. Therefore, teachers are expected to be stimulating students with members of questions related to the truth of the answers of students realizing the calculation they do so students can be more careful when solving the problem. Keywords: creative thinking ability, numeracy, assimilating and converging.